1974
DOI: 10.1128/aac.5.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Cephradine: Absorption, Excretion, and Tissue Distribution in Animals of a New Cephalosporin Antibiotic

Abstract: Metabolic studies were conducted with cephradine administred by the oral, subcutaneous, intravenous, or rectal routes to mice, rats, and dogs. Peak blood levels were usually attained in 30 to 150 min after dosing, depending on the animal species studied. Based on urinary excretion, cephradine appeared to be well absorbed after oral or subcutaneous administration; after rectal doses, cephradine was absorbed poorly. In rats and dogs given oral or intravenous doses of cephradine, about 70 to 100% of the administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…every 24 h (in drinking water) for five consecutive days in healthy and experimentally E.coli infected chickens revealed that, cephradine could be detected in liver, kidney, muscles (breast & thigh). This result slightly agreed with that recorded after oral administration to rats, cephradine was distributed widely throughout the body tissues, with the greatest concentrations in the kidneys and liver and cephradine concentrations in the kidneys and livers were about 8 and 3 times higher, respectively, than those in plasma (Weliky et al 1974). Also, oral administration of cephradine in broiler chickens twice daily for five consecutive days revealed that, treated chickens must not be slaughtered before 6 days from last dose of repeated administration of cephradine (Elsayed et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…every 24 h (in drinking water) for five consecutive days in healthy and experimentally E.coli infected chickens revealed that, cephradine could be detected in liver, kidney, muscles (breast & thigh). This result slightly agreed with that recorded after oral administration to rats, cephradine was distributed widely throughout the body tissues, with the greatest concentrations in the kidneys and liver and cephradine concentrations in the kidneys and livers were about 8 and 3 times higher, respectively, than those in plasma (Weliky et al 1974). Also, oral administration of cephradine in broiler chickens twice daily for five consecutive days revealed that, treated chickens must not be slaughtered before 6 days from last dose of repeated administration of cephradine (Elsayed et al, 2016).…”
Section: Discussionsupporting
confidence: 79%
“…Cephradine half-life is reported to range from 0.6 to 1.8 hours (Wise, 1990). The pharmacokinetics of cephradine were investigated in mice, rats, dogs (Weliky et al, 1974), human (Rattie et al, 1976;Roberts et al, 1981), foals (Henry et al, 1992), goats (El-Sayed et al, 1994) and chickens (El-Sayed et al, 2016). To our knowledge, only a few studies about disposition of cephardine in broilers are available.…”
Section: Introductionmentioning
confidence: 99%
“…Bioavailability following oral drug administration is even less well characterized. Cefaclor has been reported to have a bioavailability of 60% in the dog (Sullivan et al., 1976) while cephradine has been estimated to be 74% absorbed (Weliky et al, 1974). Although the bioavailabilities of cefadroxil and cephalexin in the dog have not been quantitated, serum levels following oral dosing compare with those of cefaclor and cephradine.…”
Section: Absorption and Distributionmentioning
confidence: 99%
“…Metabolism and Excretion-A study in mice and dogs using paper chromatographic techniques showed that no metabolites of cephradine could be found in the urine (71,73). A study in humans also could not find any metabolites of cephradine (63).…”
Section: The Value Of Vds Shown Inmentioning
confidence: 99%